Crowdsourcing with Serious Games for Defence Procurement - Oates, E P (Cranfield University, 2020)
Human Factors Engineering within UK defence procurement relies on small numbers of users picked from small user populations to help develop and test human-computer interfaces for new defence equipment. The delivered equipment is only exposed to a full assessment through mass user involvement when in service, which is the most costly point of the procurement process at which to identify any shortcomings. A prototype Electronic Warfare system interface was used to illustrate proposed new procurement processes. A ‘Serious Game’ is defined as a computer-based game used for a business purpose, and the research began by building such a game to simulate the prototype interface, which was made available through a web browser to all defence personnel. The Serious Game was developed using Open Source coding techniques and internally Crowdsourced allowing the design of this defence equipment human-computer interface to be developed and tested through a wider than usual range of user perspectives. The aim was to show how end-user experience might be enhanced and procurement costs reduced by exposing defence equipment to a wide range of users ahead of the In-Service procurement phase. This project reports on technical aspects of web-based game design and implementation, the cultural and organisational structures that affect the Crowdsourcing, and the quantitative results from controlled experiments using the Serious Game. The results show that while Open Source coding engaged with the audience at a minimal level, Crowdsourcing a Serious Game has the potential to be effective in providing a measurable benefit to defence procurement.
© Cranfield University 2020. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Human Factors Engineering; Human-Computer Interaction; Web Browser Game; Remote Unmoderated Usability Testing; Early Synthetic Prototyping